Direct steam generation for process heat applications in compound parabolic collector (CPC) - Sardeshpande, Madhavi V.; Sardeshpande, Vishal R. (11th ISES EuroSun Conference, 2017)
In recent years, CPC (Compound Parabolic Collector) is gaining its acceptance for temperature range higher than non-concentrating stationery solar collectors like flat plate collectors but lower end of temperature range of concentrating solar collectors like PTC (parabolic trough concentrators). Generally, pressurized hot water or thermal oil is used as a working fluid in the CPC. The elimination of solar tracking in CPC provides flexibility for installation and lower price point compared to other concentrating technologies with tracking. Steam is one of the universally accepted working fluid for process heat applications due to availability, nontoxic and high heat carrying capacity. Many industrial sectors such as food and beverages, textile, chemical processes etc utilize steam as a working fluid for process heat applications. Direct steam generation as a working fluid through a CPC has various operational, integration and cost advantages. The use of CPC for direct steam generation at saturation steam temperature range 105-145 degrees C (equivalent saturation pressure 0.5-3 bar (g)) can cater for low temperature process heat demand. Solar radiation intensity changes with the time of the day leading to change in heat flux for steam generation. There arc challenges for handling two phase flow (steam generation) in 'U' shaped metal tubes due to pressure drop, flow instabilities and control of steam dryness fraction under vatying solar heat flux. The focus of the present research work is to analyze a CPC system for direct steam generation. This paper discusses an experimental setup and challenges for direct steam generation. The experimental measurements will he focused on behavior of the thermal flow pattern inside the inclined metal tube at various heat flux conditions throughout the day, measurement of local heat transfer coefficients and corresponding vapor quality. Experimental data analysis and understanding will be useful to develop direct steam generation engineering schemes and its integration approach with various end-use applications.